Legal Protection Against Buyers of Cessie Receivables in Suspension of Debt Payment Obligation and Bankruptcy - Verawati, Agustina (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Transfer of accounts receivable through cessie is one of the things that is done in Indonesia. Cessie is also often carried out on receivables in cases of suspension of debt payment obligations and bankruptcy. The application of cessie in cases of suspension of debt payment obligations and bankruptcy is quite often carried out by creditors. However, Law Number 37 of 2004 concerning Suspension of Debt Payment Obligations and Bankruptcy has not further stipulated legal protection for creditors and debtors against the transfer of these receivables. Thus, legal protection for the transfer of receivables needs to be further regulated in regulations regarding suspension of debt payment obligations and bankruptcy to create legal certainty, legal benefits, and legal justice.